FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PEMBAYARAN DIVIDEN KAS - TITA DEITIANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
This research is aimed to know the influence of financial performance to management decision in paying Dividend to the stock holder. The ratio is used for research Debt to Equity Ratio, Earnings per Share, Price Earnings Ratio, Return on Asset, Current Ratio, Net Profit Margin, Inventory Turn over and Return on Equity. The research showed the Company fundamental, its financial aspect become consideration to the Dividend Policy but Other factor outside company control such as economic, government interventions, stock holder majority, and law may be main factor in determining Dividend Policy.